2001
DOI: 10.1210/jcem.86.6.7585
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Inflammatory Cytokines in Placentas from Women with Preeclampsia1

Abstract: It is postulated that inadequate remodeling of the uterine spiral arteries in preeclampsia leads to focal ischemia and generation of inflammatory cytokines, such as tumor necrosis factor (TNF alpha) and interleukins (ILs), by the placenta. Our objective was to compare TNF alpha, IL-1 alpha, IL-1 beta, and IL-6 levels in placentas from patients with preeclampsia and normal term pregnancies. Because the placenta is a large heterogeneous organ, we analyzed multiple sites per placenta. On the average, there was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…A meta-analysis of 24 studies has shown that the level of TNF-α in the maternal plasma is higher in preeclamptic women (13). However there has been no difference in placental tissue levels and TNF-α expression between preeclamptic and normal placenta (14-17); a finding that may point to the maternal origin of higher TNF-α. Several in Vitro and animal studies also support and clarify the role of TNF-α in preeclampsia.…”
Section: Discussionmentioning
confidence: 91%
“…A meta-analysis of 24 studies has shown that the level of TNF-α in the maternal plasma is higher in preeclamptic women (13). However there has been no difference in placental tissue levels and TNF-α expression between preeclamptic and normal placenta (14-17); a finding that may point to the maternal origin of higher TNF-α. Several in Vitro and animal studies also support and clarify the role of TNF-α in preeclampsia.…”
Section: Discussionmentioning
confidence: 91%
“…The concentrations of proangiogenic factors in placental tissues are significantly reduced in gestosis, while the concentrations of antiangiogenic factors are increased. Antiangiogenic factors, such as TNF-α, secreted by placental macrophages, suppress proliferation and migration of EC [1,3]. Presumably, high content of antiangiogenic and proinflammatory factors in supernatants obtained after culturing of placental explants from patients with gestosis was responsible for reduced viability and low expression of VEGF-R3 by EA.hy926 human EC.…”
Section: Resultsmentioning
confidence: 99%
“…HLFs in coculture seemingly contribute to more proinflammatory signaling, which can be reduced by addition of interleukin-10 (IL-10, an anti-inflammatory cytokine) in our system ( Figure S7, Supporting Information). [46] Given their role in inflammation, [38] and our findings highlighting the significant role of Angiopoietins in EC-pericyte signaling, we again examined Ang1/2 expression to confirm the roles of each respective stromal cell. [44] These results suggest that the interplay of stromal cells has a significant effect on the inflammatory response, which is in line with the observation that inflammatory signaling is often upregulated in placental-derived stromal cells from PE patients.…”
Section: Pericytes Increase Pe-associated Cytokine Production and Micmentioning
confidence: 99%